Creative teaching of Islamic religious knowledge in secondary schools in Brunei - Dk Nur-Ashikin bte Pg Haji Petra (Institute of Education, International Islamic University Malaysia, 2013)
An explanatory sequential design of mixed methods was applied in this research in order to describe the perceptions of religious teachers towards the creative teaching of Islamic Religious Knowledge in Brunei Muara secondary schools. 204 religious teachers answered the distributed questionnaires in Phase One and subsequently six of them were selected to be interviewed in Phase Two in order to further elaborate and clarify the research answers. The quantitative data findings in Phase One were tabulated descriptively and then the items were analyzed according to the relevant section, using Principal Component Analysis in order to extract the items that belong to the particular theme from the rotated factors. Consequently, the findings for qualitative data in Phase Two were transcribed, coded and labeled with particular themes, according to the particular section too. Then, the findings from both phases were merged for interpretation to explain the answers to the research questions of this study. The combination typologies from quantitative data in Phase One and qualitative data in Phase Two were then synthesized according to the research questions. Thus, this study explained that, based on the religious teachers' understanding, creative teaching of Islamic Religious Knowledge is synthesized into six main features: teaching pedagogy and methodology, meaningful and engaging learning process, inculcating values, using teaching technology, teaching and learning environment and a teacher's preparedness and readiness. In terms of teachers' perceptions of their current practices, creative teaching is believed to occur in eight features: applying varieties of teaching methodologies, giving concrete examples related to the students' real-life, emphasizing students' participation, using teaching technologies, the teacher's preparedness and readiness as well as employment of initiatives, the teachers' creative behaviour and lastly teachers' qualities. Finally, in terms of the obstacles and constraints of creative teaching of Islamic Religious Knowledge, the teachers perceived that there are three main factors that restrained them from teaching the subject creatively. The obstacles are, firstly, due to teachers' perceived low levels of efficacy and perseverance caused by lack of self-confidence, less capability to produce creative teaching tools, lack of lessons preparation skills, lack of skills in managing time, extra time and effort are required to make their teaching creative. The second obstacle relates to the school support and facilities comprising of school administrative work, insufficient support from the school, lack of teaching facilities and lack of resource rooms. Lastly, the third obstacle includes the students and their background which comprises of lack of students' preparation, lack of Islamic background and lack of Islamic practices. Thus, based on these points, this study has produced a significant definition of what constitutes the creative teaching of Islamic Religious Knowledge. The implications of this study are commended to the relevant authorities, as well as the teachers themselves, so that creative teaching can be applied to the subject of Islamic Religious Knowledge in order to produce a meaningful lesson.